Illocutionary Acts on Mata Najwa Talk Show on The Theme “Mata Najwa Menanti Terawan” - Nur Qonita Aulia; Didin Nuruddin Hidayat; Alek Alek (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2021)
Although studies on discourse analysis have been increasingly prevalent in the last few years, inquiries on a more specific illocutionary speech acts, particularly on the investigation of a holistic illocutionary speech acts have been relatively scarce. This study attempted to investigate the illocutionary acts used by Najwa Shihab in the episode of Mata Najwa Menanti Terawan on 28th September 2020. In this episode, Najwa Shihab discussed the latest issue regarding covid-19, which rates are still extremely high in Indonesia. This research employed a qualitative descriptive method, and to obtain the data, this study used non-participant observation. The researchers obtained the data by downloading the video related to Mata Najwa on the theme “Mata Najwa Menanti Terawan”, taking a note and, selecting the data according to the study's objective. These data were analyzed through Searle's (1976) theory. The result showed four kinds of illocutionary acts performed by Najwa Shihab, and most of the illocutionary act used by Najwa Shihab in Mata Najwa Menanti Terawan is assertive. The data show 63% assertive, 14,8% directive, 3,7% commissive, and 18,5% expressive illocutionary act. The study suggests for the subsequent research studies to explore in the wider coverage about illocutionary act, not only from the TV show but also from other aspects.